Crowd‐Sourced Databases as Essential Elements for Forest Service Partnerships and Aquatic Resource Conservation. Issue 9 (5th October 2018) - Isaak, Daniel J.; Young, Michael K.; McConnell, Callie; Roper, Brett B.; Archer, Eric K.; Staab, Brian; Hirsch, Christine; Nagel, David E.; Schwartz, Michael K.; Chandler, Gwynne L.
Abstract : High‐quality information is needed for conservation and management of aquatic resources on lands administered by the U.S. Forest Service (USFS). Information is ultimately derived from data, so the USFS maintains a series of databases that are used to describe the status and trends of aquatic habitats and biota. The databases are spatially explicit and are crowd‐sourced, meaning that distributed networks of professionals and technicians operating throughout the National Forest System collect stream and biological measurements, which are stored in central repositories. How those databases are developed is evolving and ranges from agency‐specific endeavors to collaborative projects that involve dozens of natural resource organizations and extensive user‐communities throughout the USA. The rate of data collection is accelerating and databases now often encompass millions of records, so proper archiving and maintenance by information technology specialists are necessary to maximize the utility of data for natural resource planning. Here, we describe several of the aquatic databases maintained by the USFS, applications arising from novel syntheses of databases, and the increasingly important roles databases play in collaborative partnerships and cost‐effective stewardship of aquatic resources.